2018
DOI: 10.1021/acsomega.8b02387
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbenes Derived from Guanosine: Synthesis and Evidences of Their Antiproliferative Activity

Abstract: Palladium(II) and platinum(II) complexes bearing N-heterocyclic carbenes derived from guanosine are synthesized via oxidative addition, followed by protonation in the presence of acid. Cytotoxicity of the compounds is evaluated in several cell lines. Compounds 2a, 2b, and 3a are selective for glioblastoma U251 cells and are nontoxic toward healthy human embryonic kidney (HEK293) cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 29 publications
4
56
1
Order By: Relevance
“…We have recently reported the synthesis of platinum and palladium NHCs based on guanosine derivatives [ 5 , 6 ]. Similarly, Hahn’s group described a synthetic methodology for the synthesis of guanosine and adenosine complexes with palladium [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported the synthesis of platinum and palladium NHCs based on guanosine derivatives [ 5 , 6 ]. Similarly, Hahn’s group described a synthetic methodology for the synthesis of guanosine and adenosine complexes with palladium [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hahn’s group described a synthetic methodology for the synthesis of guanosine and adenosine complexes with palladium [ 7 ]. These compounds can be obtained by C-X [ 5 , 7 ] or C-H [ 6 ] oxidative addition to Platinum(0) or palladium(0) centres. We showed that metalated nucleosides maintain the ability to form Watson–Crick base pairs, and that the presence of the metal does not influence base-pairing.…”
Section: Introductionmentioning
confidence: 99%
“…The N7 of guanine is the most nucleophilic position of DNA and RNA nucleobases 11,12 , and following acetate protection, guanosine was methylated with methyl iodide to yield 2',3',5'tri-O-acetyl-7-methylguanosine iodide (I, Scheme 2) 13 . According to previous work 14 , protection of the hydroxyl groups of 7-MeG is required. Compound I was then reacted with Pt(PPh3)4 in either toluene or dimethylformamide, affording the corresponding 7-methylguanosine hydride 1 in 56% or 31% isolated yield, respectively (Scheme 2).…”
mentioning
confidence: 99%
“…Indeed, the corresponding hydride derivative is detected, albeit in much lower yield and alongside mixture of other unidentified compounds, suggesting more than one reaction pathway. Compound 1 can be deprotected to afford compound 2 in good yields, under acidic conditions and without compromising the Pt-carbene bond or the glycosidic bond (Scheme 3) 14 . Formation of a mRNA cap analogue can also be obtained by post-functionalization of compound 3, previously reported by our group 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation